The Influence of Tax Knowledge, Taxpayer Awareness, Tax Sanctions, and Digital Payment on Taxpayer Compliance of Florist Flower Board Businesses in Palembang City. - Meliza Audry Agnesia; Andini Utari Putri; Vhika Meiriasari (STIE Amkop Makassar, 2026)
This research is a quantitative research conducted on florist flower board business actors in Palembang City. This study aims to analyze the influence of tax knowledge, taxpayer awareness, tax sanctions and digital payments on taxpayer compliance of florist flower board businesses in Palembang City. This study uses primary data through a Likert scale questionnaire involving 83 respondents. This study processes the data with the help of SPSS software. The results of this study indicate that: (a) tax knowledge has a positive and significant effect on the level of taxpayer compliance. (b) taxpayer awareness has a positive and significant effect on the level of taxpayer compliance. (c) tax sanctions have a positive and significant effect on the level of taxpayer compliance. (d) digital payments have a positive and significant effect on the level of taxpayer compliance. Based on the results of the study, it can be concluded that efforts to increase taxpayer compliance can be done by increasing understanding in the field of taxation, increasing taxpayer awareness, implementing tax sanctions effectively, and optimizing the use of digital-based tax payment systems.